2000
DOI: 10.1021/ic9912631
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Citrate Chemistry:  Syntheses, Spectroscopic Studies, and Structural Characterizations of Novel Mononuclear, Water-Soluble Manganese Citrate Complexes

Abstract: The first two mononuclear manganese citrate complexes, (NH4)4[MnII(C6H5O7)2] (1) and (NH4)5[MnIII(C6H4O7)2].2H2O (2) were synthesized in aqueous solutions near physiological pH values. They were isolated in their pure crystalline forms and characterized by elemental analyses and spectroscopic techniques, including UV/visible, electron paramagnetic resonance, Fourier transformed infrared, and magnetic susceptibility measurements. Compound 1 crystallizes in the monoclinic space group P2(1)/c, with a = 8.777(1) A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
62
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(76 citation statements)
references
References 58 publications
11
62
0
Order By: Relevance
“…In complexes 6 and 8, the citrate ligand has a non-coordinating carboxylic group (non-deprotonated), whereas the alcohol function is deprotonated. This deprotonation is promoted by Fe III , which is a hard Lewis acid, whereas with Fe II , [23] Mn II , [20] and Co II[24] the alcohol function remains protonated and hence only coordinates in monodentate mode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In complexes 6 and 8, the citrate ligand has a non-coordinating carboxylic group (non-deprotonated), whereas the alcohol function is deprotonated. This deprotonation is promoted by Fe III , which is a hard Lewis acid, whereas with Fe II , [23] Mn II , [20] and Co II[24] the alcohol function remains protonated and hence only coordinates in monodentate mode.…”
Section: Resultsmentioning
confidence: 99%
“…Doing so, the symmetry expansion of two hydrogen atoms linked to this nitrogen would lead to a non-consistent square-planar ammonium cation. In the previously reported structure [12] of 7, and also for the isostructural compounds (NH 4 ) 5 [19,20] the authors suggested that this ammonium cation was disordered. As has been underlined in a study of aluminum and gallium citrate complexes, [19b] the nitrogen and oxygen atoms have almost the same weights in the Fourier map.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Hydrothermal synthesis was performed at 100°C for 48 h. The product was filtered and rinsed with ethanol and dried at 100°C for 12 h. The polymer involved in the synthesis was fired out by sintering at 500°C in air for 2 h, which resulted in a black solid as the final product. The role of the polymer in the synthesis and the calcination of the polymeric precursor at high temperature in air are described elsewhere [9], whereas the chemistry of manganese citrate complexes is explained in [10]. Scanning electron-(SEM) and transmission electron (TEM) microscope images of the product material (Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…The two most common citrate-to-metal binding motifs are a linear citrate backbone and a "bent" citrate backbone. The manganese is found with the linear arrangement (24). Iron-citrate structures described by Matzapetakis et al describe the citrate in the "bent" arrangement for Fe 3ϩ (25).…”
Section: Discussionmentioning
confidence: 98%